Effectiveness of hypnotherapy on the level of anxiety of post-section caesarean mothers at dr Salamun tni hospital, Bandung City in 2024 - Nurhayati, Fitri; Setiowati, Tri (Science Midwifery, 2024)
Based on WHO data, the incidence of postpartum blues is 30-75%, depression in postpartum mothers is 10-15% and psychosis is 0.1%-0.2%. The brain responds to stressors by sending information to the hypothalamus which causes the adrenal glands in the cortex to produce cortisol as a stress hormone, pathologically the sympathetic nervous system responds to this by increasing blood pressure, chronic fatigue and vasoconstriction. Hypnotherapy can be an alternative for holistic prevention and treatment in reducing anxiety so as to prevent the release of the hormone cortisol in postpartum mothers. Hypnotherapy targets the parasympathetic nervous system to stimulate an increase in all functions of the sympathetic nervous system that react to anxiety. The purpose of the study was to determine the effectiveness of hypnotherapy intervention on anxiety levels and cortisol levels in the serum of post-cesarean section postpartum mothers. The research method used was a Quasy Experiment with a pretest-posttest with control group design. The study was conducted in August - September 2024 at the Dr. Salamun TNI Hospital in Bandung City. The sample in this study was 50 post-cesarean section postpartum mothers using a probability sampling method, namely the simple random sampling technique, 25 treatment respondents and 25 control respondents. The target output that will be produced is an article published in an accredited journal.